Teluk Benoa Reclamation and its Impacts - Ni Made Ayu Windu Kartika (International Journal of Glocal Tourism, 2021)
Abstract: Purpose: This article aims to analyze the impacts and community reactions to Teluk Benoa (Benoa Bay) reclamation. Research methods: This research is a descriptive analysis. The data collection method used is a literature study with a statutory regulation approach and case studies. Findings: There are positive and negative impacts that will be received by the community if Teluk Benoa reclamation is continued and the actions taken by the community to reject the plan. Implication: The impacts might be received by the community if Teluk Benoa reclamation continues, especially those on the sustainability of the surrounding environment.